On the stress concentration around a hole in an infinite plate subject to a uniform load at infinity - Batista, Milan (International journal of mechanical sciences, 2011)
In this paper stress concentration around a hole in an infinite plate that is subjected to a uniform load at infinity is considered. The stress is calculated by using a modified Muskhelishvili complex variable method. The method is illustrated by several examples of stress distribution around polygonal holes of a complex geometry utilizing the Schwartz–Chistoffel mapping function.